2019
DOI: 10.1101/830570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogen transmission from vaccinated hosts can cause dose-dependent reduction in virulence

Abstract: 2 1 Many livestock and human vaccines are leaky as they block symptoms but do not 2 2 0 *

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In particular, the vaccinal strain used in this study was shown to reduce nasal viral load and thus likely also host infectivity, as well as the duration of the infectious period with likely subsequent effects on R0. However, the results of our study also suggest that incomplete effective vaccine coverage may have less impact on the transmission dynamics than predicted by theory, as viral shedding and thus potentially infectivity of non-vaccinated individuals may be reduced if their infectious contacts are vaccinated [40]. Such indirect effects of vaccination are currently not incorporated in typical epidemiological prediction models.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In particular, the vaccinal strain used in this study was shown to reduce nasal viral load and thus likely also host infectivity, as well as the duration of the infectious period with likely subsequent effects on R0. However, the results of our study also suggest that incomplete effective vaccine coverage may have less impact on the transmission dynamics than predicted by theory, as viral shedding and thus potentially infectivity of non-vaccinated individuals may be reduced if their infectious contacts are vaccinated [40]. Such indirect effects of vaccination are currently not incorporated in typical epidemiological prediction models.…”
Section: Discussionmentioning
confidence: 58%
“…Only few studies have evaluated virus transmission using contact models (PRRSV [5,38,39]; Marek's Disease [40]; FMD [41]; Avian flu [42]; Swine flu [43]).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced VE INF anticipates that symptomatic breakthrough infections in vaccine recipients may be associated with fewer secondary transmissions than in placebo recipients, and that people who develop asymptomatic rather than symptomatic infection due to vaccination (VE SYMP ) may also be less likely to transmit. This latter observation would be expected if a vaccine mediates reduction in both symptoms and secondary transmission potential by lowering the quantity of viral shedding ( 11 ). While high VE DIS guarantees a high likelihood of individual benefit, protection of unvaccinated members of the population will also depend on VE SUSC and VE INF , as well as the velocity of a vaccination roll out program ( 8, 12 ).…”
Section: Introductionmentioning
confidence: 91%
“…Marek's disease (MD) is a serious cancer caused by Marek's disease virus (MDV), which is an oncogenic alpha herpesvirus. In addition to causing a large number of deaths, it can also cause a low feed conversion rate, weight loss, egg production reduction, and immunosuppression, leading to secondary infection of other pathogens in chickens (1)(2)(3)(4). MD was first described a hundred years ago, and after decades of research, scholars have made great efforts in understanding the genomics(5-7), serology (8), viral lifecycle (9,10), pathogenesis of cancer (11,12), vaccinology and virus mutation mechanism of MDV (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, vaccinated chickens still become infected and shed the virus into the environment (33). In addition, the vaccine itself can also replicate and shed in chickens (2,34). Thus, the live-attenuated vaccine can reduce mortality and prolong the survival time of infected chickens, but it does not significantly reduce the virus excretion rate (35).…”
Section: Introductionmentioning
confidence: 99%